The Comparative Performance of Sharia and Conventional Banks during the Pandemic: Analysis of Indonesian Banks - Tanjung, Miranda; Varianto, Gustino (Universitas Brawijaya, Indonesia, 2024)
The banking industry serves a crucial role in the economy. Unpredictable conditions, such as the COVID-19 outbreak, have had a widespread effect on global health and banking. The study examines the performance differences between conventional and Sharia banks in the pre-pandemic and during the pandemic. In addition, the study also assesses whether conventional banks are more resilient during times of crisis compared to Sharia banks or vice versa. This quantitative study uses a paired sample T-test as the research method. Secondary data from Indonesian Banking Statistics were used in this study. Data was collected two years before the COVID-19 pandemic (2018-2019) and during the COVID-19 pandemic (2020-2021). Regarding ROA and NPL, the results show that Sharia banks did better than conventional banks during the crisis. Conventional banks suffered a deteriorating CAR and NIM during 2020-2021. Even though this study shows that the financial performance ratios of both types of banks go up and down in different ways, the overall financial performance ratios are still within the limits set by Bank Indonesia.Â This study supports the central bank and financial service authority's strategy and measures in sustaining the financial service industry during a troubled time like the pandemic in 2020-2021 based on these notions. In conclusion, we emphasize the importance of bank management exercising greater caution in allocating funds to corporations and effectively monitoring their debtors to mitigate the risk of a rising non-performing loan ratio.